abd-A Regulation by the iab-8 Noncoding RNA. - Gummalla, M.; Maeda, R.K.; Castro Alvarez, J.J.; Gyurkovics, H.; Singari, S.; Edwards, K.A.; Karch, F.; Bender, W. (PLoS Genetics, 2012)
The homeotic genes in Drosophila melanogaster are aligned on the chromosome in the order of the body segments that they affect. The genes affecting the more posterior segments repress the more anterior genes. This posterior dominance rule must be qualified in the case of abdominal-A (abd-A) repression by Abdominal-B (Abd-B). Animals lacking Abd-B show ectopic expression of abd-A in the epidermis of the eighth abdominal segment, but not in the central nervous system. Repression in these neuronal cells is accomplished by a 92 kb noncoding RNA. This "iab-8 RNA" produces a micro RNA to repress abd-A, but also has a second, redundant repression mechanism that acts only "in cis." Transcriptional interference with the abd-A promoter is the most likely mechanism.